Analyzing the Cooling Rate and Its Effect on Distribution of Pattern and Size of the Titanium Diboride Particles Formed. (10th December 2021) - Senthil Kumar, P.; Chithirai, Pon Selvan; Antony Prabu, D.; Surya Prakash, G.; Murali Krishna, V.; Mohammed, Jemal Yimer
Abstract : In this work, we synthesize Al/TiB2 metal matrix composites (MMC) based on the effect of cooling rate in the melt while pouring into the permanent mold condition. The objective of this paper is to achieve the desired distribution pattern and increased TiB2 particles' size in the Al/TiB2 MMC ingot. Two halide salts, viz., potassium hexafluorotitanate (K2 TiF6 ) and potassium tetrafluoroborate (KBF4 ), are procured and measured. The two salts were mixed with the aluminium melt in the crucible, and it is stirred manually with help of a graphite rod. Because of the exothermic reaction, the melt reacts very quickly and that is what dropped the salts slowly. The salt particles were synthesized because of the exothermic reaction, and it will allow the particles to grow. The size and distribution of particles differ at different place in the MMC. An FEA tool ProCAST was used to analyze the cooling rate of the melt, and SEM is used to study the microstructure of the ingot at different places. The microstructures helped to identify the size of reinforcement in the MMC. The TiB2 particles are distributed more at this location at 810°C, and the TiB2 particles formed various clusters in this zone as 70%–80%. Also, the tribological characteristics are analyzed with the help of the results.